Functional analysis in public sector - Tunčikienė, Živilė; Buzaitė, Giedrė (Business, Management and Economics Engineering, 2010)
The main aim of the paper is to explore the theoretical aspects of functional analysis on purpose to identify the essence of functional analysis in public sector. This objective was chosen in reference to relevant problem of modern-day, i.e. inefficiency and ineffectiveness of public sector activities. The article contains functional analysis goals, tasks formed by different sources of literature; also, interpretations of the process of functional analysis are introduced. The conclusions were made that the main goal of functional analysis is to suggest an optimal set of functions that have to be performed in order to assure high quality of public services and minimal possible costs throughout all the hierarchical levels of government. Article in Lithuanian. Funkcinė analizė viešajame sektoriuje